2019
DOI: 10.1088/1361-6560/ab5b70
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance-based computed tomography metal artifact reduction using Bayesian modelling

Abstract: Metal artifact reduction (MAR) algorithms reduce the errors caused by metal implants in x-ray computed tomography (CT) images and are an important part of error management in radiotherapy. A promising MAR approach is to leverage the information in magnetic resonance (MR) images that can be acquired for organ or tumor delineation. This is however complicated by the ambiguous relationship between CT values and conventional-sequence MR intensities as well as potential co-registration issues. In order to address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…These algorithms rely on several different principles. Some approaches are based on image inpainting or sinogram inpainting 72–75 ; some others require the acquisition of additional tilted CT scans, 76 propose novel image acquisition, and reconstruction methods 77,78 ; or require the use of magnetic resonance imaging (MRI) 79,80 or megavoltage CT (MVCT) 81,82 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These algorithms rely on several different principles. Some approaches are based on image inpainting or sinogram inpainting 72–75 ; some others require the acquisition of additional tilted CT scans, 76 propose novel image acquisition, and reconstruction methods 77,78 ; or require the use of magnetic resonance imaging (MRI) 79,80 or megavoltage CT (MVCT) 81,82 …”
Section: Resultsmentioning
confidence: 99%
“…Based on the intensity values of pixels on the paired MRI slice and HU values from the artifact‐free CT slice, HU values of pixels on CT art slice are calculated. Nielsen et al evaluated their proposed MR‐based MAR algorithm (kerMAR) 80 to reduce the metal artifacts 84 . kerMAR requires aligned CT and MRI scans of the same anatomy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research-based MAR algorithms have also been evaluated for radiotherapy applications. In particular the metal deletion technique (MDT) [ 41 ], MAR with hardware adaptation [ 42 ], and ker MAR [ 43 ] have been investigated. It was shown that these algorithms can be used to reduce the errors on photon and proton range calculation during treatment planning [ 42 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple contributions amplified in the presence of metal are the main reason for artifact origin that can be from incorrect assumptions in the CT reconstruction model that is related to the image coefficients arising from X-ray projection (sinogram). 3 Diagnostic ability and accurate distinction of tissue types in the image get affected due to errors in CT numbers. Due to this, dose calculation errors during radiation therapy for cancer treatment get affected as accurate tumor localization, and characterization of surrounding tissues get hindered, affecting treatment success.…”
Section: Introductionmentioning
confidence: 99%